Pemanfaatan Limbah Cangkang Telur Sebagai Katalis Biodiesel Dari Minyak Goreng Limbah Pada UMKM Roti Pakcik Tanjung Morawa - Idris, Muhammad; Hermawan, Indra; Jufrizal, Jufrizal; Aldori, Yopan Rahmad; Supriatno, Supriatno; Harahap, Uun Novalia (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
This Community Service Program focuses on managing micro-business-scale food production waste. The activity was carried out at Pakcik Tanjung Morawa Roti MSMEs in the Tanjung Morawa area. These MSMEs produce used eggshell waste and cooking oil every day. The waste has not been managed systematically and could pollute the surrounding environment. This program aims to increase partners' awareness of the value of organic waste. The program also introduces the concept of waste utilization as an alternative energy source.  The activity's approach is educational and informative through field visits. The methods used include observation, interviews, and two-way discussions. The team conveyed the potential of eggshells as a source of calcium oxide.  Calcium oxide serves as a biodiesel catalyst from waste cooking oil. Activities do not yet include technical training or process demonstrations. The activity results showed an increase in the partners' initial understanding. Partners show interest in sustainable waste management. This program results in a mapping of potential waste and partner needs. The output of the activity is documented in reports and follow-up plans. This program is the foundation for the next stage of technology assistance. A simple approach is assessed based on the partner's capacity. Activities support waste reduction and community-based environmental education.